Bone involvement: Histopathological evidence for endoscopic management of sinonasal inverted papilloma. (19th July 2017) - Liang, Na; Huang, Zhenxiao; Liu, Honggang; Xian, Junfang; Huang, Qian; Zhou, Bing
Abstract : Objective: The aim of this study is to provide histopathological evidence for a better understanding of the excision of bone underlying tumor. Study Design: Retrospective study. Methods: Thirty patients with histopathological diagnosis of sinonasal inverted papilloma (SIP) were enrolled. All patients underwent preoperative radiography to define the tumor location. The primary tumor and underlying bone, removed during endoscopic surgery, were examined under microscope. Results: Twenty‐five of 30 specimens exhibited bony hyperostosis on computed tomography (CT) images, and 12 of 30 specimens showed evidence of bony lamellar erosion. Both coexisted in 11 cases. Half of the relapse cases (8 of 16) presented bone discontinuity on CT, which indicates a higher propensity for bone involvement when compared with primary SIP. On histopathology, 26 cases presented hyperostosis and 11 cases showed bone invasion. In total, 90% of cases covered both. Sixteen cases showed a growing tendency of inflammatory cells infiltration. Conclusion: Histopathological evidence of bone involvement indicates the importance of removal of the underlying bone at the time of endoscopic tumor resection. We hypothesized that bone involvement including bone invasion and osteogenesis may be induced by the tumor, and any microscopic lesion in the bony crevices probably indicates recurrence of SIP. Furthermore, infiltration of inflammatory cells may facilitate bone involvement and cause recurrence. Level of Evidence: NA. Laryngoscope, 127:2703–2708, 2017